Isolated eosinophilic mastitis: a rare breast disease mimicking malignancy - Gondwal, Anjula; Srivastav, Srijan (International Journal of Research in Medical Sciences, 2021)
Eosinophilic mastitis is a rare benign breast pathology which presents with lump breast and can mimic malignancy. So far eight reported cases have been found in literature review. All cases were associated with peripheral eosinophilia and systemic involvement except one. Isolated eosinophilic mastitis in the absence of peripheral eosinophilia or systemic involvement is a very rare presentation. Being one of the rare cases, prompted us to take up this case in our present study. A 40-year-old lady presented with progressively enlarging, slightly painful swelling in left breast of 15 days duration with no other relevant past and family history. The clinical differential diagnosis of mastitis and carcinoma was suggested. Aspiration cytology was reported as benign breast disease- fibroadenosis. Imaging studies undertaken were inconclusive. Case managed surgically with wide local excision. Post-surgical tissue specimen was subjected to histopathology examination and was diagnosed as eosinophilic mastitis. A prolonged follow-up revealed no recurrence.